O Centro de Educação e Cultura Indígena (CECI) da aldeia Tekoa Pyau (Jaraguá - São Paulo/SP): a cultura Guarani na escola de educação infantil e a atuação dos educadores indígenas - Santos, Chirley Maria de Souza Almeida (2016)
This current work, analyzing narratives and information collected through the means of interviews and observation, examined the work realized by the professionals of education of the CECI-Jaraguá (center of education and indigenous culture, school belonging to the network of education of the municipality of Sao Paulo, Brazil). The reflections made with base at the data had as reference the fact that such educational center is an instrument to the strengthening of the traditional Guarani culture, transforming in school content their cosmology and customs resulted from the way of life, besides the knowledge that the elderly of the tribe carry on. The presence of the school in the community is also justified by the necessity of the indigenous understand the world of the juruá (non indigenous). It was verified that the processes of preservation of customs and native beliefs taken away in an institution (the school) that does not make part of the Guarani culture, as long as the education of the children was historically promoted in the interaction and integration of them in the activities of the adults, show the transformation such of the tradition as the school, without meaning the loss of the cultural identity. For this reason, the concept of frontier by Fredrik Barth was fundamental to the interpretation of the data